2016
DOI: 10.1051/epjconf/201613101002
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties towards the island of stability

Abstract: Abstract. The structure of the nuclei of the heaviest elements is discussed with emphasis on single-particle properties as determined by decay and inbeam spectroscopy. The basic features of production of these nuclei using fusion evaporation reactions will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Studying nuclear structure of superheavy elements (SHE) (Z > 100) is an important area of research taking nuclear physics to unexplored territory and potentially leading to hypothetical island of stability [1][2][3][4][5][6]. The sources of experimental information are very limited since the SHE are not found in nature but produced at accelerators at very low production rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying nuclear structure of superheavy elements (SHE) (Z > 100) is an important area of research taking nuclear physics to unexplored territory and potentially leading to hypothetical island of stability [1][2][3][4][5][6]. The sources of experimental information are very limited since the SHE are not found in nature but produced at accelerators at very low production rate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all produced isotopes are neutron-poor and have short lifetimes (see, e.g. reviews [1][2][3][4][5][6]). Using atomic spectroscopy to measure isotope shift (IS) and hyperfine structure (hfs) is one of the promising methods to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…The study of super heavy elements (SHE), Z > 100, which are not found in nature has been a constant frontier of nuclear and atomic physics for the past century [1,2]. The discovery and study of these exotic elements is of great interest at both microscopic and cosmological scales, particularly in relation to the existence of the fabled island of stability which is the shell model's promise of stable super heavy elements and the property of the underlying exotic nuclei [2][3][4][5]. The study of SHEs also gives insight into fundamental physics such as correlation and relativistic interactions in atomic systems.…”
Section: Introductionmentioning
confidence: 99%